Synthesis of silver nanoparticles and their fungal resistance against Pyricularia oryzae causing blast disease in rice cultivation - Thanh Hải, Nguyễn Thị; Mỹ Phương, Tôn Nữ; Thu Thủy, Nguyễn Thị; Thái Hòa, Trần (Hue University Journal of Science: Natural Science, 2019)
In this study, silver nanoparticles (AgNPs) were synthesized using the chemical reduction method with sodium citrate as a reducing agent and alginate as a protecting agent. The parameters affecting the synthesis of silver nanoparticles, namely silver nitrate concentration, alginate concentration, sodium citrate concentration, and temperature of the reaction, were studied. The formation of AgNPs, morphology, and structure of the synthesized materials were analyzed using UV-Vis spectroscopy, scanning electron microscopy, transmission electron microscopy, high-resolution transmission microscopy, and X-ray diffraction. AgNPs products have a high inhibitory effect on Pyricularia oryeza, causing rice blast.